K-On Application Concept Design (K3 Oriented and Implementation using Participatory Design and Usability Testing Methods - Padhil, Ahmad; Rauf, Nurhayati; Saputra, Muh Dafha Reza Ramadhan; Rini, Asih Setyo; Suryapranatha, Dicky (Center for Study and Journal Management FTI UMI, 2024)
Indonesia as a developing country has become a country with a systematic infrastructure focus, with constant infrastructure growth making Indonesia a development country. Infrastructure, especially in the context of building or construction, has a linear relationship with the condition of construction workers, where construction workers are one of the main driving forces in the sustainability of development in Indonesia. However, the central role of this worker is not always followed by the worker's obedience to the applicable regulations in this case K3 construction. Work accidents in the construction sector increase every year, recorded as many as 114,148 throughout 2018 although it decreased to 77,295 cases in 2019, not diminishing the indication that construction workers should receive special treatment to reduce the number of work accidents. The development of technology is the basis for thinking for innovation in making platforms to cover almost every aspect of life, so the implementation of technology in an effort to provide special education to construction workers is expected to be optimal. The design of this concept uses participatory design and usability testing, to involve workers and stakeholders directly in the design process. The output of this research is an application concept design along with the percentage of effectiveness and efficiency that has gone through a pilot test process to end users, in this case construction workers and other stakeholders